Methodology of Ultrasonographic Examination of the Anterolateral Ligament of the Knee Joint - Kostrub, O.O.; Kotiuk, V.V.; Osadcha, L.Ye.; Luchko, R.V.; Didukh, P.V.; Vadziuk, N.S. (TERRA ORTHOPAEDICA, 2020)
Summary. Injury of the anterolateral ligament (ALL) accompanies more than half of the anterior cruciate ligament ruptures. However, the uncertainty in the anatomy of ALL raises many questions regarding its visualization on ultrasound. There are also very few ultrasonographic studies of the ALL in the scientific literature in the era of MRI and CT. Objective: to determine the optimal methods and techniques for identifying and improving the visualization of the ALL with ultrasonography. Materials and Methods. ALL ultrasonography was performed in 30 healthy volunteers without pathology of the knee joint on both knee joints using a linear high-frequency sensor (ACUSON NX2 Elite, 10 MHz) at different angles of bending and rotation. Results. Ultrasonography was able to visualize the ALL in all 30 patients as a fibrillar anisotropic structure. The distinctiveness of the ALL was significantly different between patients. It was easiest to find and visualize it well with an extended knee joint, and to assess the integrity and tension when bending the knee joint at an angle of 60° and in the maximum internal rotation of the lower leg. A clearly visible tubercle was revealed by ultrasonography at the site of attachment of the ALL to the tibia in 100% of patients, which has not been described previously and greatly facilitates its finding. There was a history of a violation of the integrity of the cortical layer at the site of attachment of the ALL to the tibia in 26.67% of patients without pathology of the knee joint and injuries. Ultrasonographic identification of the two-layer structure of the ALL failed. The femoral part of the ALL is usually woven into the initial part of the fibular collateral ligament and cannot be separated ultrasonographically from it. In all 30 patients with relatively healthy knee joints without traumatic pathology, the ALL in the contralateral joints looked similar, without statistically significant deviations in their morphometric parameters. Conclusions. Ultrasonography visualizes the tibial and femoral parts of the ALL particularly but not exclusively during movements; however, it almost does not show meniscus bundles separately. For a better visualization of the ALL and assessment of its integrity, we recommend starting its research with an extended knee joint, and then performing functional tests by alternating internal and external rotation of the lower leg at different angles of flexion of the knee joint. The starting point of the ALL is the origin of the fibular collateral ligament from the lateral condyle of the femur, and the reference point of attachment is the tubercle on the anterolateral surface of the tibia posterior to Gerdy tubercle uncovered by us with ultrasonography in all the patients, which is an important reference point that allows faster, easier, and more confident localization of the ALL tibial portion insertion site. On a healthy contralateral joint, the ALL can serve as a reference for comparison if its rupture is suspected.